Phytochemical and Chromatographic Studies of Medicinal Plant Terminalia arjuna (Roxb.) Wight & Arn. Stem Bark and Inner Wood Combinations for Judicious Utilization. Issue 1 (2nd January 2023) - Deepak, M.; Sulaiman, C.T.; Sreejith, V.S.; Balachandran, Indira
Abstract: Terminalia arjuna, is an important medicinal plant mainly used for cardiovascular ailments in the traditional Indian system of medicine Ayurveda. The stem bark of T. arjuna is generally employed in Ayurvedic formulations. The present study undertakes the possibilities of judicious utilization of stem bark and inner wood combinations of T. arjuna instead of bark alone in herbal medicines. Different combinations of bark and inner wood portions were prepared and extracted. Preliminary phytochemical analyses by qualitative tests, and quantitative estimations of total phenolics, and flavonoid contents revealed predominant results in bark extract. Anti-oxidant activities like DPPH, and ABTS radical scavenging assays were carried out and bark extract showed leading results and the combination sample also showed promising values. Comparative chemical profiling of the samples was done using High-performance thin layer chromatography to identify and quantify major chemical constituents. Flavonoids such as catechin, epicatechin, and phenolic acid, gallic acid were identified by HPTLC profiling, in all samples. On quantification of gallic acid, the bark and sample BS1 showed promising results when compared with other combination samples. The identified compounds were proven with medicinal activities against cardiovascular-related ailments. The present study concluded that BS1 (75:25) of bark and wood combination could be used instead of bark (B) for medicinal preparations without affecting the quality so the 25% usage of bark can be reduced and 25% of the stem can be saved from waste. The study will be beneficial for Ayurvedic industries using the bark T. arjuna for medicinal preparation since the wastage of wood can be reduced without affecting the quality of medicine. GRAPHICAL ABSTRACT: UF0001